Qualidade de vida de familiares de crianças portadoras da Síndrome de Down: perspectiva de mães - Mapelane, Lenia (2011)
Parental expectations on an unborn child rise towards the ideal of a child in the enjoyment of good physical and mental health, which ensures its continuity. At its birth a child with Down syndrome (DS) these expectations can vanish, initiating adaptive experiences, which in some cases may be dysfunctional. This research aims to understand quality of life (QOL) in terms of mothers of children with DS. We chose an approach based on phenomenological theoretical and qualitative method and interpretation of data on the reflection around the concept of QOL that allows the understanding of subjective perception and conscious of the person on the vicissitudes of their biopsychosocial experiences. The survey was conducted in Maputo, Mozambique from December 2010 to February 2011. We used a personal data questionnaire to collect demographic and biographical information and a semistructured individual interview recorded in sound recording. This study was approved by the Ethics Committee in Research of the Pontifical Catholic University of Sao Paulo by Protocol 338/2010. Four mothers whose children with DS collaborated in the research. In the context studied it is confirmed, as in other studies that sociocultural factors and the lack of professionals in communicating the diagnosis to parents may be barriers for acceptance of a child with Down syndrome. From the psychological point of view these factors can disrupt parental expectations and increase their uncertainty about their role, leading them to experience adaptive nonfunctional behavior. These factors along with scarcity of resources and an inefficient network support and services, contribute to increase mental and physical burden of the interviewed mothers, which interferes negatively in the domains of their QOL. Yet, in the context of this study, it is possible to notice a stigma in relation to the child with DS, and the widow. This is based on certain beliefs and socio-cultural attitudes